Treemap algorithm for dynamic stormwater infiltration movement into soil surface - Reli, Siti Nurbaidzuri; Yusoff, Izham Mohamad; Lateh, Habibah; Ujang, Uznir (2015)

(untitled)
Plenty of researches have been carried out focusing on the real time movement of objects such as the movement of animals, humans, vehicle, clouds and water. However, real time movement of water in soil particles that leads to other natural processes (landslides and soil erosion) should be emphasized and given adequate attention through 3 Dimensional (3D) modelling of this event to provide prediction and analysis. To date, 3D research has focused on city models and Building Information Modeling (BIM) but studies that involve 3D modelling of natural processes (movement of air and fluid) is rare. Water flows in many directions and it is most suitably represented in form of 3D. Applying 2 Dimensional (2D) tools to 3D situation limits the scientist works in many ways in terms of understanding, viewing and analysing. 2D model focuses solely on x axis (horizontal) and y axis (vertical). This research applies tree algorithm to model a dynamic stormwater infiltration movement spatially that flow through the soil by additional z axis which represents the depth of the soil. Tree algorithm is used to re-class and provides hierarchical depth of the soil where the depth are divided into five hierarchies (40cm, 80cm, 120cm, 160cm and 20cm) based on subsurface flow wetting range. Required information concerning rainfall and soil types were translated into a model based on the infiltration process occurred at the study area. Although most of the previous studies use Tree algorithm for 2D analysis, this study highlights the capability of the algorithm in 3D analysis by producing hierarchy for soil depth.